Bioavailability of Curcumin in Various Nanoformulations: A Critical Review - Lalong, Paulus Risan F; Refdi, Cesar Welya; Une, Suryani; Sayuti, Mohammad; Iswadi, Didik (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
The critical review aimed to assess the enhancement of curcumin bioavailability through nanoformulation-based delivery systems, summarize comparative pharmacokinetic and in vivo safety data, and identify significant obstacles to the clinical translation of curcumin. This study identified articles from Scopus, Elsevier (via ScienceDirect), and PubMed that were published between 2015 and 2025. We used keyword combinations such as curcumin, nanoformulation, nanoparticles, bioavailability, pharmacokinetics, toxicity/safety, and clinical translation to identify them. Furthermore, a comparison was made between peer-reviewed studies that were eligible based on the type of nanoformulation, the reported fold-increase in bioavailability, tolerability in vivo, and the limitations of translation. Nanoparticles (e.g., PLGA, chitosan), solid lipid nanoparticles, micelles, nanoemulsions, nanogels, cyclodextrin complexes, phytosomes, dendrimers, metallic nanoparticles, niosomes, and exosomes exhibit mechanisms that enhance solubility, provide protection against degradation, improve permeability, and facilitate sustained or targeted delivery. The data demonstrate that various nanoformulations can enhance systemic exposure from moderate to substantial levels, depending on the formulation and study design, with lipid-polymer-based systems often exhibiting significant enhancements. Studies generally report acceptable safety at therapeutic doses; however, dose dependence, formulation-specific effects, limited long-term human data, manufacturing scalability, and evolving regulatory requirements continue to constrain clinical adoption. Enhance curcumin's bioavailability and therapeutic efficacy; however, standardized manufacturing, thorough safety assessment, and robust clinical trials are necessary to facilitate its integration into standard practice.Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well BeingSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 17: Partnerships for the Goals